2014
DOI: 10.1093/hmg/ddu259
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study and mouse expression data identify a highly conserved 32 kb intergenic region between WNT3 and WNT9b as possible susceptibility locus for isolated classic exstrophy of the bladder

Abstract: Bladder exstrophy-epispadias complex (BEEC), the severe end of the urorectal malformation spectrum, has a profound impact on continence as well as sexual and renal functions. It is widely accepted that for the majority of cases the genetic basis appears to be multifactorial. Here, we report the first study which utilizes genome-wide association methods to analyze a cohort comprising patients presenting the most common BEEC form, classic bladder exstrophy (CBE), to identify common variation associated with risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 45 publications
2
24
0
1
Order By: Relevance
“…For example in our study, the expression of Wnt3a is significantly elevated (fold change 7.53) at ejaculation (EJ group), and Wnt9b and Cdkn1a are up-regulated at ejaculation that is stimulated by 8-OH-DPAT and inhibited by dapoxetine treatment. The data reported by previous studies 40 have confirmed that Wnt3a suppresses cancer cell proliferation, and both Wnt9b and Cdkn1a suppress cancer progression41, 42, 43.…”
Section: Discussionmentioning
confidence: 56%
“…For example in our study, the expression of Wnt3a is significantly elevated (fold change 7.53) at ejaculation (EJ group), and Wnt9b and Cdkn1a are up-regulated at ejaculation that is stimulated by 8-OH-DPAT and inhibited by dapoxetine treatment. The data reported by previous studies 40 have confirmed that Wnt3a suppresses cancer cell proliferation, and both Wnt9b and Cdkn1a suppress cancer progression41, 42, 43.…”
Section: Discussionmentioning
confidence: 56%
“…Some previous studies have linked GWAS results to evidence from mice. [43][44][45] By systematically linking well-powered GWAS summary results with corresponding phenotypes in thousands of mice and using additional databases to evaluate their expression during murine renal development, our approach is very comprehensive.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were recruited in person by experienced physicians trained in the diagnosis of CBE and details of the recruitment process were outlined elsewhere. 14,24 Sequence Analysis Blood or saliva samples were obtained from patients and isolation of genomic DNA from blood was performed using a Chemagic Magnetic Separation Module I (Chemagen, Baesweiler, Germany). Genomic DNA from saliva samples was extracted by using the Oragene DNA Kit (DNA Genotek Inc., Kanata, Canada).…”
Section: Subjectsmentioning
confidence: 99%